Fertility Transition in Burundi: Contribution of Individual and Contextual factors among Women in Union - Singoye, Emmanuel; Manirakiza, Rene; Djourdebbe, Bouba Franklin; Toyi, Aloys; Bassinga, Herve (European Scientific Journal, ESJ, 2025)
Against the backdrop of uneven demographic transitions in sub-Saharan Africa, grasping the dynamics of fertility at a national level poses a significant challenge to the development of effective public policies. This study aims to ascertain the impact of individual and contextual factors on the fertility of union women in Burundi. To accomplish this, the study employs an analytical approach that systematically examines the repercussions of these factors. The analysis is based on data from the 2010 and 2016-2017 Demographic and Health Surveys (DHS). The 2016–17 DHS-III survey covered a sample of 16,620 households and focused on women aged 15–49. The study was conducted in accordance with a two-stage sampling plan to ensure representation at the national level and in urban and rural areas. A similar methodology was employed for the 2010 EDSB-II survey, which was conducted on a sample of 9,024 households. The study also incorporated representative samples from urban and rural areas, with biomarker tests administered in 50% of selected households. This approach enabled differentiated analyses to be performed by region and area of residence. While the overall quality of the data was satisfactory, the integration of specific modalities, including age at first marriage and the economic status of women in union, was necessitated by the small size of certain subgroups within the sample. Furthermore, while the decomposition method has been demonstrated to be an effective tool for identifying sources of variation in fertility, it is important to acknowledge its limitations. Notably, the method cannot distinguish precisely between individual and contextual effects, which may consequently introduce bias into the estimates. The findings, derived from the application of rudimentary and sophisticated decomposition techniques, suggest that the observed decline in fertility in Burundi is predominantly due to a performance effect. Furthermore, multivariate analyses demonstrate that economic activity, educational attainment, women’s decision-making power and region of residence significantly influenced the reduction in fertility among union women between 2010 and 2016-2017. This study provides a detailed understanding of the mechanisms that led to the decline in fertility in Burundi, clearly distinguishing between the composition and performance effects. The central role of women’s empowerment in this process is emphasized. Consequently, enhancing public policies that facilitate women’s access to education, formal employment, and participation in household decision-making is recommended to support the ongoing demographic transition.